Genomic comparison of Salmonella enterica serovars and Salmonella bongori by use of an S. enterica serovar typhimurium DNA microarray. - Chan, K; Baker, S; Kim, C; Detweiler, C; Dougan, G; Falkow, S (2003)
The genus Salmonella consists of over 2,200 serovars that differ in their host range and ability to cause disease despite their close genetic relatedness. The genetic factors that influence each serovar's level of host adaptation, how they evolved or were acquired, their influence on the evolution of each serovar, and the phylogenic relationships between the serovars are of great interest as they provide insight into the mechanisms behind these differences in host range and disease progression. We have used an Salmonella enterica serovar Typhimurium spotted DNA microarray to perform genomic hybridizations of various serovars and strains of both S. enterica (subspecies I and IIIa) and Salmonella bongori to gain insight into the genetic organization of the serovars. Our results are generally consistent with previously published DNA association and multilocus enzyme electrophoresis data. Our findings also reveal novel information. We observe a more distant relationship of serovar Arizona (subspecies IIIa) from the subspecies I serovars than previously measured. We also observe variability in the Arizona SPI-2 pathogenicity island, indicating that it has evolved in a manner distinct from the other serovars. In addition, we identify shared genetic features of S. enterica serovars Typhi, Paratyphi A, and Sendai that parallel their unique ability to cause enteric fever in humans. Therefore, whereas the taxonomic organization of Salmonella into serogroups provides a good first approximation of genetic relatedness, we show that it does not account for genomic changes that contribute to a serovar's degree of host adaptation.